2012
DOI: 10.1094/pdis-03-12-0290-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of ‘Candidatus Phytoplasma asteris’ Affecting Woody Hosts (Fraxinus uhdei, Populus nigra, Pittosporum undulatum, and Croton spp.) in Colombia

Abstract: Phytoplasmas of the 16SrVII group in ornamental Fraxinus uhdei trees (1) growing in different cities of the Colombian Andes have been reported (2). In surveys made in Bogotá during March and May 2011, symptoms suggestive of phytoplasma infection were observed in ornamental woody species: Croton spp. (Euphorbiaceae), Pittosporum undulatum (Pittosporaceae) and Populus nigra (Salicaceae) trees, growing close to infected F. uhdei (Oleaceae). Symptoms included witches' broom, yellowing, dieback, epicormic sprouts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Phytoplasma fraxini' subgrupo 16SrVII-A en Bogotá, infectando árboles de Croton spp., P. nigra y P. undulatum obtenida por PCR anidada (Figura 3 A), secuenciación (Tablas 2 y 3, Figura 4) y RFLP (Figuras 3B y 3C) en los mismos árboles en los cuales en un trabajo anterior se demostró la presencia de fitoplasmas del grupo 16SrI (Perilla et al, 2012, Franco-Lara, 2013. Los resultados presentados en este trabajo indican que frecuentemente los fitoplasmas del grupo 16SrVII se encuentran en infecciones mixtas con fitoplasmas del grupo 16SrI en los árboles evaluados.…”
Section: Discussionunclassified
“…Phytoplasma fraxini' subgrupo 16SrVII-A en Bogotá, infectando árboles de Croton spp., P. nigra y P. undulatum obtenida por PCR anidada (Figura 3 A), secuenciación (Tablas 2 y 3, Figura 4) y RFLP (Figuras 3B y 3C) en los mismos árboles en los cuales en un trabajo anterior se demostró la presencia de fitoplasmas del grupo 16SrI (Perilla et al, 2012, Franco-Lara, 2013. Los resultados presentados en este trabajo indican que frecuentemente los fitoplasmas del grupo 16SrVII se encuentran en infecciones mixtas con fitoplasmas del grupo 16SrI en los árboles evaluados.…”
Section: Discussionunclassified
“…They live in the phloem tissue of plants and are transmitted by insect vectors [ 1 ]. It has been reported that phytoplasmas are the pathogens associated with a large number of diseases in several hundred economically important plants [ 2 , 3 ], and Paulownia plants are no exception [ 4 , 5 ]. Paulownia witches’ broom (PaWB) disease, caused by the phytoplasma in the subgroup 16SrI-D of aster yellows [ 1 , 6 ], has resulted in extensive losses in the yields of paulownia timber, leading to significant economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…In Colombia, as in other parts of the world, phytoplasma diseases are recognized due to their increasing impact on crops and ornamental plants, either because they are new diseases, known diseases with uncertain aetiology or diseases with new geographical distributions (Bertaccini & Duduk, ). In the last 15 years, several new phytoplasma diseases in urban trees have been described in Bogotá (Griffiths et al ., ; Franco‐Lara & Filgueira, ; Perilla‐Henao et al ., ; Perilla‐Henao & Franco‐Lara, ; Franco‐Lara & Perilla Henao, ), but until now there was no information about the insect vectors present in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplasmas of groups 16SrI (‘ Ca . Phytoplasma asteris’) and 16SrVII are the predominant strains detected in the trees of Bogotá (Perilla‐Henao et al ., ; Perilla‐Henao & Franco‐Lara, ), although groups 16SrV, 16SrIX and 16SrXII have also been detected in L. styraciflua (authors’ unpublished data). The incidence of this disease varies among tree species, but it ranges between 36% in Croton spp.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation